2015
DOI: 10.1155/2015/963152
|View full text |Cite
|
Sign up to set email alerts
|

Mimicking Peroxidase Activity by a Manganese(II) Complex Involving a New Asymmetric Tetradentate Ligand Containing Both Amino and Imino Groups

Abstract: The asymmetric ligand (E)-4-bromo-2-(((2-((5-bromo-2-hydroxybenzyl)(methyl)amino)ethyl)imino)methyl)phenol has been prepared by a novel seven-step route. All organic compounds isolated in each step have been characterised by elemental analysis, infrared and1H NMR spectroscopy, and mass spectrometry. Interaction of this ligand with manganese has been investigated employing an electrochemical method. This method leads to the formation of a neutral manganese(II) complex7in high yield and purity. The complex has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…For example, Peŕez-Otero et al reported a Mn (II) complex with a symmetric tetradentate ligand containing both amino and imino groups that exhibited peroxidase-like activity. 33 In another work, Kim and Lee developed a peroxidase-like catalyst through the self-assembly of histidyl bolaamphiphiles coordinated with Mn 2+ ions to detect glucose through cascade catalysis with glucose oxidase (GOx). 34 GSH i.e γ-L-glutamyl-L-cysteinyl-glycine is a tripeptide antioxidant biothiol synthesized in the cell that protects cells from oxidative damage and toxic xenobiotic electrophiles and maintains redox homeostasis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Peŕez-Otero et al reported a Mn (II) complex with a symmetric tetradentate ligand containing both amino and imino groups that exhibited peroxidase-like activity. 33 In another work, Kim and Lee developed a peroxidase-like catalyst through the self-assembly of histidyl bolaamphiphiles coordinated with Mn 2+ ions to detect glucose through cascade catalysis with glucose oxidase (GOx). 34 GSH i.e γ-L-glutamyl-L-cysteinyl-glycine is a tripeptide antioxidant biothiol synthesized in the cell that protects cells from oxidative damage and toxic xenobiotic electrophiles and maintains redox homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there are several literature reports of Mn (II) species acting as peroxidase-mimic nanozymes that motivated this work to utilize a phthalocyanine molecule with Mn as the metal center (oxidation state of Mn in MnPc is +2). For example, Pérez-Otero et al reported a Mn (II) complex with a symmetric tetradentate ligand containing both amino and imino groups that exhibited peroxidase-like activity . In another work, Kim and Lee developed a peroxidase-like catalyst through the self-assembly of histidyl bolaamphiphiles coordinated with Mn 2+ ions to detect glucose through cascade catalysis with glucose oxidase (GOx) …”
Section: Introductionmentioning
confidence: 99%
“…Peroxidases catalyse oxidation of a broad range of substrates by hydrogen hydroxide, so they may be successfully used for different industrial processes since peroxidases are capable of degrading aromatic rings in lignin, dyes, and polycyclic aromatic hydrocarbons [15,16,20,21]. In this sense, dyes are regarded as one of the most important contaminants to be removed from the industrial effluents, and peroxidases arise as a way to treat these pollutants.…”
Section: Introductionmentioning
confidence: 99%